Incidence of epigeal nest-building termites in Brachiaria pastures in the Cerrado = Incidência de térmitas de ninhos epígeos em pastagens de Brachiaria no Cerrado - Maria Inês Lopes de Oliveira; Didier Brunet; Danielle Mitja; Wellington dos Santos Cardoso; Norton Pólo Benito; Maria de Fátima Guimarães; Michel Brossard (Acta Scientiarum: Agronomy, 2011)
This study aimed to determine the number of termite epigeal nests and estimate the soil turning capacity of termites in cultivated pasture environments and in a native vegetation area. Surveys were conducted in four areas: three pasture areas and a Cerrado area, measuring 5 ha each. For each nest, the height, the perimeter and diameter at the base were measured. The volume of each mound was calculated. Turned soil was determined by randomly sampling 30 termite mounds in a pasture area for bulk density determinations. The mean number oftermite mounds per ha was 408; the highest number of termite nests (672 per ha) was found in the 10-year-old pasture. In terms of termite mound density, there was no difference between the Cerrado, 3-year-old pasture, and 3-year-old intercropped pasture treatments. The total area occupied by termite nests ranged from 0.4 to 1.0%. The mean bulk density of the nest materials was 1.05 g cm-3. The total nests volume ranged from 4 to 11 m3 ha-1. The total mass of the soilturned by the termites ranged from 3.4 to 13.4 ton. ha-1. O presente trabalho teve como objetivo determinar o número de ninhos epígeos e estimar a capacidade de revolvimento do solo pelos térmitas em ambientes de pastagens cultivadas e uma área nativa de Cerrado. Foram feitos levantamentos em quatro áreas, sendo três de pastagem e uma de Cerrado com 5 ha cada. Para cada ninho, foram mensurados a altura, o perímetro basal e diâmetro na base. Foi calculado o volume de cada montículo. Para determinar a densidade do solo mobilizado foi feita amostragem ao acaso em ninhos epígeos numa área de pastagem. O número médio de ninhos epígeos por ha foi de 408, o maior número de cupinzeiros está na pastagem dez anos (672 ninhos). Em termos de densidade média de ninhos epígeos não houve diferença entre os tratamentos: Cerrado, pastagem três anos e pastagem consorciada trêsanos. A área total ocupada pelos ninhos epígeos variou de 0,4 a 1 %. A densidade do solo mobilizado pelos térmitas foi de 1,05 g cm-3. O volume total de solo mobilizado variou de 4 a 11 m3 ha-1. A massa total de solo mobilizado pelos térmitas foi de 3,4 to 13,4 t ha-1.